PEMODELAN DAN SIMULASI PEMBANGKIT LISTRIK TENAGA BAYU SISTEM ON-GRID MENGGUNAKAN MATLAB SIMULINK - Cristian, Yosep; Silalahi, Eva Magdalena; Widodo, Bambang (Prodi Teknik Elektro FT UKI, 2024)
In this study, the authors analyzed the variables of research in the form of wind turbine mechanical power results based on wind speed varies, as well as the results of current, voltage and power of permanent magnet synchronous generators based on wind speed varies. This study aims to determine the results of mechanical power output in wind turbines, the power output of generators, and the efficiency of On-Grid Power Plant Systems. The method used in this study uses literature study method and associative method. Where the method of literature study to collect literature on wind power plants, associative method to determine the relationship of several variables studied. Based on the research conducted on the simulation, the mechanical power output of wind turbine at minimum wind speed (cut-in) 3.38 m/sec is 27.68 W and at maximum wind speed (rated) reaches 103.6 W, and the voltage, current and power generated by the generator at minimum speed is 75.29 V, 2.81 A, and 9.89 W, while at maximum wind speed reaches 75.37 V, 2.7 A, and 77.54 W. The maximum efficiency generated by On-Grid PLTB is 75% at a maximum wind speed of 7.63 m/sec.